Autoimmunity and effector recognition in Arabidopsis thaliana can be uncoupled by mutations in the RRS1-R immune receptor - Newman, Toby E (The New phytologist, 2019)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.